THE VARIATION OF ADHESIVE QUANTITY ON PARTICLE BOARDS FROM ARECA NUT SHELL AND MAHANG WOOD POWDER - Puluhulawa, Indriyani (Journal of Green Science and Technology, 2018)
Particle boards are the solution to the productivity problems of the timber industry which deficiency of raw materials. The manufacture of particle boards from Areca nut shell and Mahang wood powder is an effort to develop existing types of particle boards as well as efforts to utilize areca nut waste and increase the economic value of local wood (Mahang wood). The aim of this study was to determine the effect of quantity variations of adhesive to the composition of the mixture. There are four types of particle board variations are made with the same composition of areca nut and powder but different quantity of adhesive. The determination of physical properties and mechanical properties of particle boards based on JIS A 5908 2003 or SNI 03-2105-2006. The result was an increase in physical and mechanical properties on the particle board whose content of adhesive was greater. The other sides, the mechanical properties of all variations of particle board do not fulfill the existing standards.Keywords: Areca nut particle board, Mahang wood powder particle board, adhesive content